2015
DOI: 10.1161/circoutcomes.115.001767
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Implications of Level-of-Care at Tertiary Heart Centers Compared With Other Hospitals After Resuscitation From Out-of-Hospital Cardiac Arrest

Abstract: Background-Studies have found higher survival rates after out-of-hospital cardiac arrest and admission to tertiary heart centers. The aim was to examine the level-of-care at tertiary centers compared with nontertiary hospitals and the association with outcome after out-of-hospital cardiac arrest. Methods and Results-Consecutive out-of-hospital cardiac arrest patients (n=1078) without ST-segment-elevation myocardial infarction admitted to tertiary centers (54%) and nontertiary hospitals (46%) were included (200… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
38
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 62 publications
(41 citation statements)
references
References 32 publications
2
38
0
1
Order By: Relevance
“…Kajino et al [38] found that the survival of patients after OHCA with presumed cardiac etiology without field ROSC who were transported to critical care medical centers (i.e., tertiary-care centers in Japan) was better than the survival of those transported to non-critical care center (i.e., non-tertiary-care centers) in the Osaka area, Japan. Similar studies were recently reported from the Copenhagen area in Denmark [39,40]. In addition, Stub et al [22] previously reported that a hospital factor significantly associated with survival was treatment at hospitals with 24 h cardiac interventional services.…”
Section: Hospital Case-volumes and The Level-of-caresupporting
confidence: 74%
See 2 more Smart Citations
“…Kajino et al [38] found that the survival of patients after OHCA with presumed cardiac etiology without field ROSC who were transported to critical care medical centers (i.e., tertiary-care centers in Japan) was better than the survival of those transported to non-critical care center (i.e., non-tertiary-care centers) in the Osaka area, Japan. Similar studies were recently reported from the Copenhagen area in Denmark [39,40]. In addition, Stub et al [22] previously reported that a hospital factor significantly associated with survival was treatment at hospitals with 24 h cardiac interventional services.…”
Section: Hospital Case-volumes and The Level-of-caresupporting
confidence: 74%
“…Thus, the authors concluded that a high frequency of post-cardiac arrest care in an ICU seemed to be associated with improved outcome of cardiac-arrest patients [14]. These studies suggest that admission to high level-of-care centers and intensive care admission after OHCA is associated with a significantly higher survival rate even after adjustment for prognostic factors including pre-arrest comorbidity [14,22,[38][39][40].…”
Section: Hospital Case-volumes and The Level-of-carementioning
confidence: 97%
See 1 more Smart Citation
“…A recent review of utilisation of TTM for patients with non-shockable rhythm conclude that further studies are needed to identify which patients may benefit for the treatment (12). In terms of selection bias, evidence suggests that the level of care indeed matters with higher survival rates following OHCA at tertiary heart centres with e.g., available intensive care, coronary interventions and pacemaker-implantation (13).…”
Section: Ttm For Patients Resuscitated From a Nonshockable Rhythmmentioning
confidence: 99%
“…87,88 OHCA victims should be considered for transport to a specialist cardiac arrest center as part of a wider regional system of care.…”
Section: Systemsmentioning
confidence: 99%